Archive of the University of Coimbra: management, communication and dissemination of information. Issue 1 (January 2020) - Gomes, Liliana Isabel Esteves
Abstract : The Archive of the University of Coimbra (AUC) holds and manages the rich documentation produced and received by the University, which was founded by King Dinis in 1290. As a specialized service with the function of District Archive, it also manages the fonds collected from its geographical area. The organization and functions of the Archive are discussed; specifically the articles list the projects carried out by AUC, particularly those relating to the communication and dissemination of the information it holds (for example digital content availability and online research tools). Current concerns, as well as the challenges for the near future, are examined. Results of a study of the AUC using formal case study methodology, confirm that the Archive was, in the past, connected to the "patrimonial values" of the memory of the organization and the community of Coimbra District, rather than pursuing the policy of dissemination and contribution to the community that it does today.